Edukasi Cara Menyikat Gigi dengan Benar Dalam Pencegahan Karies Gigi pada Siswa di SD N 1 Kedamaian - Nurani, Rahmawati Dian; Khomsah, Ida Yatun (Kolaborasi: Jurnal Pengabdian Masyarakat, 2025)
Abstract   Introduction: Dental caries is one of the most common oral health problems among elementary school-aged children, both globally and in Indonesia, including in areas like Bandar Lampung. The high prevalence of caries is influenced by various factors, such as poor oral hygiene, consumption of sugary foods, and improper or irregular toothbrushing habits. The lack of education and supervision from parents and schools also exacerbates this condition. Therefore, promotive and preventive efforts are needed, including education on proper tooth brushing from an early age. Elementary schools are a strategic place to instill the habit of brushing through a fun and interactive approach. Educational interventions by health workers, particularly nurses, are crucial for increasing children's knowledge and skills in maintaining dental health, thereby reducing the incidence of tooth decay and improving their overall quality of life. Objective: To provide direct education and training on correct tooth brushing techniques in accordance with dental and oral health standards. Method: The method of this activity is carried out using lecture, discussion, demonstration and question and answer methods. Result: This activity was successfully implemented, involving 75 students who participated in the community service program. Education regarding tooth decay prevention had a significant impact, as the students learned how to brush their teeth properly, the appropriate time to brush, and what foods to avoid to prevent tooth decay Conclusion: The results of the evaluation given to participants showed an increase in knowledge and skills in the right time and technique for brushing their teeth.